Life-threatening intoxication with methylene bis(thiocyanate): clinical picture and pitfalls. A case report - Braun, Claude; Birck, Rainer; Singer, Manfred V.; Schnülle, Peter; Woude, Fokko J. van der; Löhr, J.-Matthias (BMC emergency medicine, 2006)
Methylene bis(thiocyanate) (MBT) is a microbiocidal agent mainly used in industrial water cooling systems and paper mills as an inhibitor of algae, fungi, and bacteria.